Evaluating alternative targeting of social assistance in fragile settings - Abay, Kibrom A.; Berhane, Guush; Gilligan, Daniel O.; Tafere, Kibrom; Taffesse, Alemayehu Seyoum (AEA RCT Registry, 2023)
This research project aims to address three research objectives. First, we aim to evaluate the performance of alternative targeting approaches including Proxy Means test (PMT), Community-Based Targeting (CBT) and Peer Targeting (PT) in fragile and conflict settings. We measure their relative performance in terms of identifying the poor. Second, we test the performance of alternative variants of community-based targeting approaches under different selection conditionalities and budget constraints. We evaluate the impact of alternative designs to CBT on the breadth and depth of social assistance transfers distributed to members of the community. Third, we evaluate decision-making and negotiation processes in CBT when real incentives are involved and in the absence of actual cash transfers.